Use of absorbable hemostatic gelatin sponge in postoperative care of the vascular pedicle of interpolated flaps - Alan Rodriguez Muñiz; Bruno Quirino dos Santos; Luis Eduardo Redondo; Lucas Dal Pozzo Sartori; Milton Paulo de Oliveira; Carlos Oscar Uebel (Revista Brasileira de Cirurgia Plástica, 2017)
Interpolated flaps are among the most important and functional flaps in reconstructive plastic surgery, representing a safe option even in the most difficult cases. The pedicle of the interpolated flap requires a dressing to avoid bleeding and local contamination. This dressing often fails to prevent minor bleedings, which occurs within the first 24-48 hours. As a result, it needs to be continuously changed, from three to five times on average. The technique proposed in this study consists in a direct application of a GELFOAM® layer. This is subsequently wrapped with petroleum gauze to prevent bleeding of the open area in the pedicle flap, improving hemostasis and reducing the manipulation of the vascular pedicle.